Lithium manganese iron phosphate positive electrode material and preparation method thereof
By using calcium lignin sulfonate as a dispersant and carbon source in the preparation process of lithium manganese iron phosphate positive electrode material, and combining the use of urea to establish a nitrogen and sulfur co-doped conductive carbon network, the material's conductivity and cycle life are solved The problem has achieved efficient electrochemical performance improvement.
Patent Information
- Application Number
- CN202411672930.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-21
AI Technical Summary
The electronic conductivity and ionic conductivity of lithium manganese ferrophosphate cathode material are low, and the conductivity of manganese is poor, which leads to the battery being prone to polarization and reduced cycle life. It is easy to have Jahn-Teller effect when the manganese content is high, affecting the stability of the material. performance and capacity retention.
Calcium lignin sulfonate is used as a dispersant and carbon source to disperse raw materials evenly in the precursor slurry, and lithium manganese iron phosphate positive electrode material is prepared by spray drying and sintering, and carbon is coated in situ through urea as a nitrogen source. Establish a conductive carbon network co-doped with nitrogen and sulfur.
It improves the uniformity and conductivity of the material, shortens the grinding time, enhances the electrochemical performance, and can meet the needs of large-scale charging and discharging.
Smart Images

Figure BDA0005146345700000101 
Figure BDA0005146345700000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] Lithium manganese iron phosphate (LMFP) has attracted widespread attention due to its advantages such as abundant raw materials, low cost, good safety and environmental friendliness. However, there are still many challenges in the research and development of LMFP, such as the low electronic conductivity and ionic conductivity of LMFP; the poor conductivity of manganese, the battery is prone to polarization, and the cycle life is reduced. Especially when the manganese content is too high, the Jahn-Teller effect is prone to occur, affecting the material stability and capacity retention rate. In order to solve the above problems, researchers have adopted a variety of methods to improve the performance of LMFP, such as nano-sizing, carbon coating and ion doping. Reducing the size of material particles to nanometers can effectively shorten the lithium ion migration path and improve the lithium ion migration efficiency. However, as the size of material particles decreases, serious particle agglomeration will occur during the production and pulping process, affecting the uniformity of the material and thus affecting the battery performance. Uniformly coating the carbon material on the surface of LMFP particles can improve the external conductivity of the material. At the same time, carbon coating can also inhibit the dissolution of manganese ions and reduce the influence of the Jahn-Teller effect on the battery capacity and cycle stability. Although this method can improve its shortcomings, it still cannot meet people's demand for high-rate charging and discharging. Therefore, it is necessary to seek a simple, low-cost and efficient technical solution, and it is of great significance to develop a lithium manganese iron phosphate positive electrode material with good conductivity and high capacity.
[0003] In view of this, this invention is proposed. Summary of the invention
[0004] The first purpose of the present invention is to provide a method for preparing a lithium iron manganese phosphate positive electrode material, which improves the problems of uneven particle dispersion and long grinding time required during the preparation of the lithium iron manganese phosphate positive electrode material, and improves the uniformity and electrochemical properties of the lithium iron manganese phosphate positive electrode material.
[0005] The second object of the present invention is to provide a lithium manganese iron phosphate positive electrode material with excellent uniformity, electrical conductivity and conductivity.
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0007] In a first aspect, the present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0008] S1, grinding a lithium source, a phosphorus source, an iron source, a manganese source, calcium lignin sulfonate, urea, a second carbon source and a solvent to obtain a precursor slurry;
[0009] S2. Spray-drying and sintering the precursor slurry in sequence to obtain the lithium manganese iron phosphate positive electrode material.
[0010] Furthermore, step S1 includes at least one of the following features (1) to (5):
[0011] (1) The lithium source includes at least one of lithium dihydrogen phosphate, lithium carbonate, lithium acetate and butyl lithium;
[0012] (2) the phosphorus source comprises at least one of lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate and ammonium dihydrogen phosphate;
[0013] (3) The iron source includes at least one of ferrous sulfate, ferrous oxalate, ferric phosphate and ferrous phosphate;
[0014] (4) The manganese source includes at least one of manganese sulfate, manganese pyrophosphate, manganese dioxide and manganese tetraoxide;
[0015] (5) The second carbon source includes at least one of glucose, sucrose and citric acid.
[0016] Furthermore, in step S1, the mass of the calcium lignin sulfonate is 15% to 30% of the theoretical output of lithium iron manganese phosphate; the mass of the urea is 4% to 6% of the theoretical output of lithium iron manganese phosphate.
[0017] Furthermore, in step S1, the mass of the second carbon source is 0.5% to 3% of the theoretical yield of lithium manganese iron phosphate.
[0018] Furthermore, in step S1, the molar ratio of the Fe element in the iron source to the Mn element in the manganese source is (2-8): (2-8); the molar ratio of the Li element in the lithium source to the P element in the phosphorus source is (1-1.1): 1; the ratio of the total molar number of the Fe element in the iron source and the Mn element in the manganese source to the molar number of the P element in the phosphorus source is (0.95-1): 1.
[0019] Further, in step S1, the grinding time is 5 to 8 hours;
[0020] And / or, the average particle size of the solid particles in the precursor slurry is 0.35-0.41 μm.
[0021] Furthermore, in step S2, the inlet temperature of the spray drying is 210-230°C, and the outlet temperature is 85-100°C.
[0022] Furthermore, in step S2, the sintering includes: heating to 400-600°C at a rate of 1-5°C / min, then heating to 700-800°C at a rate of 5-15°C / min and heat preservation for 9-11 hours.
[0023] Furthermore, in step S2, after the sintering, the step further includes: crushing to an average particle size of 0.8 to 1.5 μm.
[0024] In a second aspect, the present invention further provides a lithium iron manganese phosphate positive electrode material, which is prepared by the preparation method of the lithium iron manganese phosphate positive electrode material as described above.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The preparation method of the lithium manganese iron phosphate positive electrode material of the present invention adds calcium lignin sulfonate as a dispersant during the preparation of the precursor slurry, which can effectively disperse various raw materials in the grinding process in the solvent, effectively inhibit the agglomeration of particles, thereby improving the uniformity of the material and shortening the grinding time.
[0027] 2. The present invention uses calcium lignin sulfonate as a carbon source, which effectively improves the conductivity of the lithium manganese iron phosphate positive electrode material; at the same time, calcium lignin sulfonate is used as a sulfur source and urea is used as a nitrogen source to in-situ coat carbon and establish a nitrogen and sulfur co-doped conductive carbon network, which helps to increase the active sites of the material, reduce the electrochemical reaction energy barrier of the material, and improve charge transfer and Li + The diffusion rate of lithium manganese iron phosphate can be increased, which promotes electron migration and improves the electrochemical performance of lithium manganese iron phosphate cathode materials. DETAILED DESCRIPTION
[0028] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0029] The following is a detailed description of a lithium manganese iron phosphate positive electrode material and a preparation method thereof of the present invention.
[0030] In some embodiments of the present invention, a method for preparing a lithium manganese iron phosphate positive electrode material is provided, comprising the following steps:
[0031] S1, grinding a lithium source, a phosphorus source, an iron source, a manganese source, calcium lignin sulfonate, urea, a second carbon source and a solvent to obtain a precursor slurry;
[0032] S2. The precursor slurry is spray-dried and sintered in sequence to obtain a lithium manganese iron phosphate positive electrode material.
[0033] In the preparation method of the lithium manganese iron phosphate positive electrode material of the present invention, calcium lignin sulfonate is used as a dispersant. Calcium lignin sulfonate is a multi-component high molecular polymer anionic surfactant, which has both a hydrophobic group and a hydrophilic group. Adding calcium lignin sulfonate in the preparation process of the precursor slurry can effectively disperse various raw materials in the grinding process evenly in the solvent, thereby improving the uniformity of the material; in addition, its high molecular polymer structure can also be evenly wrapped on the surface of the particles, effectively inhibiting the particle agglomeration phenomenon through the steric hindrance effect, thereby greatly shortening the grinding time.
[0034] The present invention adopts calcium lignin sulfonate as a carbon source. Calcium lignin sulfonate itself contains up to 30% reducing sugars and is a sustainably renewable carbon source with the advantages of low cost and high reserves. It is also rich in aromatic structures and multiple functional groups, which can play a role in regulating morphology and element doping after carbonization, and can form defects during the carbonization process, effectively improving the conductivity of lithium manganese iron phosphate positive electrode materials.
[0035] The present invention uses calcium lignin sulfonate as a sulfur source and urea as a nitrogen source to in-situ coat carbon. The nitrogen and sulfur atoms doped in the carbon layer will destroy the originally ordered structure of the carbon layer. The combination of the two can establish an effective nitrogen and sulfur co-doped conductive carbon network, which helps to increase the active sites of the material, reduce the electrochemical reaction energy barrier of the material, and improve charge transfer and Li + The diffusion rate of lithium manganese iron phosphate can be increased, which promotes electron migration and improves the electrochemical performance of lithium manganese iron phosphate cathode materials.
[0036] The method for preparing the lithium iron manganese phosphate positive electrode material of the present invention is simple to operate and is suitable for large-scale production. The prepared lithium iron manganese phosphate positive electrode material has good electrochemical properties and has broad application prospects.
[0037] In some embodiments of the present invention, in step S1, the lithium source includes at least one of lithium dihydrogen phosphate, lithium carbonate, lithium acetate and butyl lithium.
[0038] In some embodiments of the present invention, in step S1, the phosphorus source includes at least one of lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate and ammonium dihydrogen phosphate.
[0039] In some embodiments of the present invention, in step S1, the iron source includes at least one of ferrous sulfate, ferrous oxalate, ferric phosphate and ferrous phosphate.
[0040] In some embodiments of the present invention, in step S1, the manganese source includes at least one of manganese sulfate, manganese pyrophosphate, manganese dioxide and manganese tetraoxide.
[0041] In some embodiments of the present invention, in step S1, the second carbon source includes at least one of glucose, sucrose and citric acid.
[0042] In some embodiments of the present invention, in step S1, the solvent includes but is not limited to water.
[0043] In some embodiments of the present invention, in step S1, the mass of calcium lignin sulfonate is 15% to 30% of the theoretical output of lithium iron manganese phosphate; the mass of urea is 4% to 6% of the theoretical output of lithium iron manganese phosphate; typically but not limiting, for example, the mass of calcium lignin sulfonate can be 15%, 18%, 20%, 22%, 25%, 28%, 30% of the theoretical output of lithium iron manganese phosphate, or a range consisting of any two thereof; the mass of urea can be 4%, 4.5%, 5%, 5.5%, 6% of the theoretical output of lithium iron manganese phosphate, or a range consisting of any two thereof.
[0044] The theoretical yield of lithium iron manganese phosphate is: the theoretical yield (mass) of lithium iron manganese phosphate calculated from the added amounts of lithium source, phosphorus source, iron source and manganese source.
[0045] Calcium lignin sulfonate is used as a dispersant to improve grinding efficiency and make particles uniform; both calcium lignin sulfonate and urea can be used as the first carbon source, where lignin is additionally used as a sulfur source and urea is additionally used as a nitrogen source, and nitrogen and sulfur co-doping improves conductivity. Calcium lignin sulfonate and urea are used as the first carbon source. If the amount of calcium lignin sulfonate and urea added is small, the carbon content is low and the electrical properties are poor; if the amount of calcium lignin sulfonate and urea added is large, the carbon content is high and the electrical properties are good, but the compaction is low.
[0046] In some embodiments of the present invention, in step S1, the mass of the second carbon source is 0.5% to 3% of the theoretical yield of lithium iron manganese phosphate; typically but not limiting, for example, the mass of the second carbon source can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3% of the theoretical yield of lithium iron manganese phosphate or a range of any two thereof.
[0047] In some embodiments of the present invention, in step S1, the molar ratio of the Fe element in the iron source to the Mn element in the manganese source is (2-8): (2-8); the molar ratio of the Li element in the lithium source to the P element in the phosphorus source is (1-1.1): 1; the ratio of the total molar number of the Fe element in the iron source and the Mn element in the manganese source to the molar number of the P element in the phosphorus source is (0.95-1): 1.
[0048] In some embodiments of the present invention, in step S1, the grinding time is 5 to 8 hours; typically but not limiting, for example, the grinding time can be 5 hours, 6 hours, 7 hours, 8 hours or a range of any two thereof.
[0049] In some embodiments of the present invention, in step S1, grinding includes sand grinding.
[0050] In some embodiments of the present invention, in step S1, the average particle size D of the solid particles in the precursor slurry is 50 It is 0.35~0.41μm.
[0051] In some embodiments of the present invention, in step S2, the inlet temperature of the spray drying is 210-230°C, and the outlet temperature is 85-100°C.
[0052] In some embodiments of the present invention, in step S2, sintering includes: heating to 400-600°C at a rate of 1-5°C / min, then heating to 700-800°C at a rate of 5-15°C / min and heat preservation for 9-11 hours; sintering includes: heating to a first temperature at a first rate, then heating to a second temperature at a second rate and heat preservation; the first rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or a range of any two thereof; the first temperature can be 400°C. , 450℃, 500℃, 550℃, 600℃ or a range consisting of any two of them; the second rate can be 5℃ / min, 7℃ / min, 9℃ / min, 11℃ / min, 13℃ / min, 15℃ / min or a range consisting of any two of them; the second temperature can be 700℃, 720℃, 740℃, 760℃, 780℃, 800℃ or a range consisting of any two of them; the insulation treatment time can be 9h, 10h, 11h or a range consisting of any two of them.
[0053] In some embodiments of the present invention, in step S2, sintering is performed under a protective atmosphere, preferably, the protective atmosphere includes a nitrogen atmosphere.
[0054] In some embodiments of the present invention, in step S2, after sintering, the step further includes: crushing to an average particle size D 50 0.8~1.5μm.
[0055] In some specific embodiments of the present invention, in step S2, the precursor slurry is spray-dried in sequence to obtain a precursor; the precursor is sintered to obtain a sintered powder; and the sintered powder is crushed to obtain a lithium manganese iron phosphate positive electrode material.
[0056] In some embodiments of the present invention, a lithium iron manganese phosphate positive electrode material is also provided, which is prepared by the above-mentioned preparation method of the lithium iron manganese phosphate positive electrode material.
[0057] The lithium iron manganese phosphate positive electrode material prepared by the preparation method of the lithium iron manganese phosphate positive electrode material in the present invention has excellent uniformity, electrical conductivity and conductivity.
[0058] Example 1
[0059] The method for preparing the lithium manganese iron phosphate positive electrode material provided in this embodiment comprises the following steps:
[0060] S1. Weigh 690 g of lithium carbonate, 1885 g of lithium dihydrogen phosphate, 1383 g of manganese tetraoxide, 2708 g of iron phosphate, 169 g of sucrose, 825 g of calcium lignin sulfonate, 363 g of urea and 9 kg of pure water and grind them in a sand mill to obtain a precursor slurry; grind until the average particle size of the solid particles in the precursor slurry is D 50 The particle size was 0.40 μm, and the grinding time was 6 h;
[0061] S2, spray drying the precursor slurry to obtain a precursor; the inlet air temperature of the spray drying is 220°C, and the outlet air temperature is 90°C;
[0062] The precursor was placed in a box-type atmosphere furnace, and under the protection of a circulating nitrogen atmosphere, the temperature was first raised to 450°C at a rate of 2°C / min, and then raised to 760°C at a rate of 5°C / min for 9 hours. After natural cooling, a sintered powder was obtained; the sintered powder was crushed to an average particle size of D 50 The particle size was 1.1 μm, and lithium manganese iron phosphate positive electrode material was obtained.
[0063] Example 2
[0064] The method for preparing the lithium manganese iron phosphate positive electrode material provided in this embodiment comprises the following steps:
[0065] S1. Weigh 690 g of lithium carbonate, 1885 g of lithium dihydrogen phosphate, 1383 g of manganese tetraoxide, 2708 g of iron phosphate, 169 g of sucrose, 904 g of calcium lignin sulfonate, 250 g of urea and 9 kg of pure water and grind them in a sand mill to obtain a precursor slurry; grind until the average particle size of the solid particles in the precursor slurry is D 50 The particle size was 0.40 μm, and the grinding time was 5 h.
[0066] S2, spray drying the precursor slurry to obtain a precursor; the inlet air temperature of the spray drying is 220°C, and the outlet air temperature is 90°C;
[0067] The precursor was placed in a box-type atmosphere furnace, and under the protection of a circulating nitrogen atmosphere, the temperature was first raised to 450°C at a rate of 2°C / min, and then raised to 760°C at a rate of 5°C / min for 9 hours. After natural cooling, a sintered powder was obtained; the sintered powder was crushed to an average particle size of D 50 The particle size was 1.1 μm, and lithium manganese iron phosphate positive electrode material was obtained.
[0068] Example 3
[0069] The method for preparing the lithium manganese iron phosphate positive electrode material provided in this embodiment comprises the following steps:
[0070] S1. Weigh 690 g of lithium carbonate, 1885 g of lithium dihydrogen phosphate, 1383 g of manganese tetraoxide, 2708 g of iron phosphate, 170 g of sucrose, 824 g of calcium lignin sulfonate, 303 g of urea and 9 kg of pure water and grind them in a sand mill to obtain a precursor slurry; grind until the average particle size of the solid particles in the precursor slurry is D 50 The particle size was 0.38 μm, and the grinding time was 8 h.
[0071] S2, spray drying the precursor slurry to obtain a precursor; the inlet air temperature of the spray drying is 220°C, and the outlet air temperature is 90°C;
[0072] The precursor was placed in a box-type atmosphere furnace, and under the protection of a circulating nitrogen atmosphere, the temperature was first raised to 450°C at a rate of 2°C / min, and then raised to 760°C at a rate of 5°C / min for 9 hours. After natural cooling, a sintered powder was obtained; the sintered powder was crushed to an average particle size of D 50 The particle size was 1.1 μm, and lithium manganese iron phosphate positive electrode material was obtained.
[0073] Example 4
[0074] The preparation method of the lithium manganese iron phosphate positive electrode material provided in this embodiment refers to Example 1, the only difference being that in step S1, the mass of urea is 242 g.
[0075] Example 5
[0076] The preparation method of the lithium iron manganese phosphate positive electrode material provided in this embodiment refers to Example 1, the only difference being that in step S1, the mass of calcium lignin sulfonate is 1650 g.
[0077] Comparative Example 1
[0078] The preparation method of the lithium manganese iron phosphate positive electrode material provided in this comparative example refers to Example 1, except that in step S1, calcium lignin sulfonate and urea are not added, and the grinding time is 10 hours in total.
[0079] Comparative Example 2
[0080] The preparation method of the lithium iron manganese phosphate positive electrode material provided in this comparative example refers to Example 1, except that in step S1, calcium lignin sulfonate is not added, and the grinding time is 10 hours in total.
[0081] Comparative Example 3
[0082] The preparation method of the lithium manganese iron phosphate positive electrode material provided in this comparative example refers to Example 1, except that in step S1, urea is not added and the grinding time is 6 hours in total.
[0083] Test Example 1
[0084] The compaction density of the lithium iron manganese phosphate positive electrode materials prepared in each embodiment and each comparative example was tested, and the results are shown in Table 1.
[0085] Compaction density: Use FTYS-10KN automatic powder compaction density meter, weigh 1g±0.01g of sample each time, apply pressure of 3T, and maintain pressure for 30s.
[0086] The lithium manganese iron phosphate positive electrode materials prepared in the embodiments and comparative examples were used to prepare positive electrode sheets, assemble batteries, and perform performance tests. The results are shown in Table 1.
[0087] The battery assembly process and test conditions are as follows:
[0088] Battery assembly: The lithium manganese iron phosphate positive electrode material, conductive agent, and binder are uniformly dispersed in N-methylpyrrolidone at a mass ratio of 94:3:3 to obtain an electrode slurry, and the slurry is evenly coated on aluminum foil, vacuum dried at 100°C for 12 hours, and then rolled and sliced to obtain a positive electrode sheet. Metal lithium is used as the negative electrode, LB315 is selected as the electrolyte, and the diaphragm is a commercial diaphragm. CR2032 button batteries are assembled in a glove box with argon as the protective gas;
[0089] Electrochemical performance test: The relevant electrochemical performance of the battery is tested by the blue electric test system. The test conditions are constant current and constant voltage charging (cut-off voltage 4.5V, cut-off current 0.05A), and constant current discharge (cut-off voltage 2.5V).
[0090] Table 1
[0091]
[0092]
[0093] From the data in Table 1, it can be seen that calcium lignin sulfonate and urea as carbon sources are conducive to improving the conductivity of lithium manganese iron phosphate positive electrode materials, with a 0.1C discharge specific capacity of >150mAh / g and a 0.1C first efficiency of >90%; in addition, calcium lignin sulfonate as a high molecular polymer dispersant effectively shortens the grinding time during grinding, and the time taken for the slurry to reach the required particle size is shortened by 40%. The preparation process of lithium iron phosphate prepared in the embodiment of the present invention is less time-consuming, and can have both a higher compaction density and excellent electrochemical performance, which is better than the comparative example.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The steps include: S1, grinding a lithium source, a phosphorus source, an iron source, a manganese source, calcium lignin sulfonate, urea, a second carbon source and a solvent to obtain a precursor slurry; S2. Spray-drying and sintering the precursor slurry in sequence to obtain the lithium manganese iron phosphate positive electrode material.
2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S1, at least one of the following features (1) to (5) is included: (1) The lithium source includes at least one of lithium dihydrogen phosphate, lithium carbonate, lithium acetate and butyl lithium; (2) the phosphorus source comprises at least one of lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate and ammonium dihydrogen phosphate; (3) The iron source includes at least one of ferrous sulfate, ferrous oxalate, ferric phosphate and ferrous phosphate; (4) The manganese source includes at least one of manganese sulfate, manganese pyrophosphate, manganese dioxide and manganese tetraoxide; (5) The second carbon source includes at least one of glucose, sucrose and citric acid.
3. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: In step S1, the mass of the calcium lignin sulfonate is 15% to 30% of the theoretical output of lithium iron manganese phosphate; the mass of the urea is 4% to 6% of the theoretical output of lithium iron manganese phosphate.
4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 3, characterized in that: In step S1, the mass of the second carbon source is 0.5% to 3% of the theoretical yield of lithium manganese iron phosphate.
5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 4, characterized in that: In step S1, the molar ratio of the Fe element in the iron source to the Mn element in the manganese source is (2-8): (2-8); the molar ratio of the Li element in the lithium source to the P element in the phosphorus source is (1-1.1): 1; the ratio of the total molar number of the Fe element in the iron source and the Mn element in the manganese source to the molar number of the P element in the phosphorus source is (0.95-1):
1.
6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: In step S1, the grinding time is 5 to 8 hours; And / or, the average particle size of the solid particles in the precursor slurry is 0.35-0.41 μm.
7. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: In step S2, the inlet temperature of the spray drying is 210-230°C, and the outlet temperature is 85-100°C.
8. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: In step S2, the sintering includes: heating to 400-600°C at a rate of 1-5°C / min, then heating to 700-800°C at a rate of 5-15°C / min and maintaining the temperature for 9-11 hours.
9. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: In step S2, after the sintering, the process further comprises: crushing the sintered product to an average particle size of 0.8 to 1.5 μm.
10. A lithium manganese iron phosphate positive electrode material, characterized in that: The lithium manganese iron phosphate positive electrode material is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Cited By
Lithium manganese iron phosphate battery and recovery method of positive electrode material of lithium manganese iron phosphate battery
CN120328502A